COMPETENCIES OF GERMAN LANGUAGE TEACHERS IN INDONESIA AND VIETNAM BASED ON COMMON EUROPEAN FRAMEWORK OF REFERENCE FOR LANGUAGES (CEFR) - Pratomo Widodo; Akbar K Setiawan; Le Hoai An (LITERA, 2016)
This study aims to (1) identify and compare the language competencies of German language teachers in Indonesia and Vietnam, and (2) identify the factors attributable totheir competency levels. This was a qualitative descriptive study. The data were collectedby means of questionnaires. The study shows that, based on the CEFR, the competencies ofGerman language teachers in Vietnam are in the B2 level, while those of German languageteachers in Indonesia are in the B1 level. The low competencies of German languageteachers in Indonesia are caused by the language attrition and the lack of opportunitiesto receive language training.